Functional parameter measurements in children with ataxia telangiectasia. (30th August 2019) - Shenhod, Efrat; Benzeev, Bruria; Sarouk, Ifat; Heimer, Gali; Nissenkorn, Andreea
Abstract : Aim: To collect preliminary functional data on ataxia telangiectasia and create a disease specific scale: the Ataxia Telangiectasia Functional Scale (ATFS). Method: Retrospective information on patients with ataxia telangiectasia referred to the Assistive Technology Unit was included. Functional mobility scales (the Gross Motor Function Classification System [GMFCS] and the Functional Mobility Scale [FMS]‐5, FMS‐50, FMS‐500) and activities of daily living [ADL] parameters were recorded. We created a 51‐point ATFS, that consisted of three ambulation items adapted for ataxia telangiectasia in the frame of FMS (home, school, outdoors), five ADL items, and one schooling item. Results: Twenty‐seven participants (17 males, 10 females; mean age 10y 8mo [SD 5y 1mo], range 1y 9mo–25y 6mo), were enrolled; 168 measurements were recorded. Patients walked at a mean age of 1 year 4 months (SD 5y 4mo) and lost ambulatory capacity at 8 years 8 months (SD 2y 1mo). GMFCS level and FMS‐5, FMS‐50, FMS‐500 assessments correlated with age (Spearman's correlations r =0.555, −0.617, −0.639, −0.662 respectively, p <0.01 for all), but plateaued after 12 years of age. ATFS mean score was 37.46 (SD 7.88) and increased with age (Spearman's correlation r =0.585, p <0.01). The scale showed three stages of disease progression. Interpretation: In this pilot study we show longitudinal functional data of ambulation and ADL skills in ataxia telangiectasia, and created a framework for a functional scale. This functional scale closely approximated disease course, but further validation is required. What this paper adds: The Gross Motor Function Classification System and the Functional Mobility Scale are ill‐suited for ataxia telangiectasia assessments. Three functional mobility scales (home, school, outdoors) suited to ataxia telangiectasia were created. The Ataxia Telangiectasia Functional Scale (ATFS) combines mobility and items of activities of daily living. The ATFS closely approximates the three‐stage progression of the disorder. What this paper adds: The Gross Motor Function Classification System and the Functional Mobility Scale are ill‐suited for ataxia telangiectasia assessments. Three functional mobility scales (home, school, outdoors) suited to ataxia telangiectasia were created. The Ataxia Telangiectasia Functional Scale (ATFS) combines mobility and items of activities of daily living. The ATFS closely approximates the three‐stage progression of the disorder. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Perlman on page 157 of this issue. Video Podcast: https://www.youtube.com/watch?v=S7e99UGliCg&feature=youtu.be Resumen: Mediciones de parámetros funcionales en niños con ataxia telangiectasia: Objetivo: Recopilar datos funcionales preliminares sobre la ataxia telangiectasia y crear una escala específica de la enfermedad: la escala funcional de la ataxia telangiectasia (ATFS). Método: Se incluyó información retrospectiva sobre pacientes con ataxia telangiectasia remitidos a la Unidad de Tecnología Asistiva. Se registraron las escalas de movilidad funcional (el sistema de clasificación de la función motora gruesa [GMFCS] y la escala de movilidad funcional [FMS‐5, FMS‐50, FMS‐500]) y los parámetros de las actividades de la vida diaria [ADL]. Creamos un ATFS de 51 puntos, que constaba de tres elementos de asistencia a la deambulación adaptados para la ataxia telangiectasia según los requerimientos de FMS (hogar, escuela, exteriores), cinco elementos de ADL y un elemento de escolarización. Resultados: Se reclutaron 27 participantes (17 varones, 10 mujeres; edad media 10a 8m[DE 5a 1m], rango 1a 9m– 25a 6m); se registraron 168 mediciones. Los pacientes caminaron a una edad promedio de 1 año y 4 meses (DE 5 y 4 meses) y perdieron la capacidad ambulatoria a los 8 años y 8 meses (DE 2 y 1 meses). Las evaluaciones GMFCS y FMS‐5, FMS‐50, FMS‐500 se correlacionaron con la edad (correlaciones de Spearman r = 0, 555, –0, 617, –0, 639, –0, 662 respectivamente, p <0, 01 para todos), pero se estancaron después de los 12 años de edad. La puntuación media de ATFS fue 37, 46 (SD 7, 88) y aumentó con la edad (correlación de Spearman r = 0, 585, p <0, 01). La escala mostró tres etapas de progresión de la enfermedad. Interpretación: En este estudio piloto, mostramos datos funcionales longitudinales de ambulación y habilidades de ADL en la ataxia telangiectasia, y creamos un marco para una escala funcional. Esta escala funcional se aproximó mucho al curso de la enfermedad, pero se requiere validación adicional. Resumo: Medidas de parâmetros funcionais em crianças com ataxia telangiectasia: Objetivo: Coletar dados funcionais prelimiares sobre ataxia telangiectasia e criar uma escala específica para a doença: a Escala Funcional de Ataxia Telangiectasia (EFAT). Método: Informações retrospectivas sobre pacientes com ataxia telangiectasia encaminhados para a Unidade de Tecnologia Assistiva foram incluídas. Escalas de mobilidade funcional (o Sistema de Classificação da Função Motora grossa [GMFCS] e a Escala de Mobilidade Funcional [FMS]‐5, FMS‐50, FMS‐500) e parâmetros de atividades da vida diária [AVD] foram registrados. Uma EFAT de 51 pontos foi criada, consistindo de três itens de deambulação adaptados para ataxia telangiectasia na estrutura da FMF (casa, escola, comunidade), cinco itens de AVDs, e um item sobre escolaridade. Resultados: Vinte e sete participantes (17 do sexo masculino, 10 nomes do sexo feminino; média de idade 10a 8m [DP 5a 1m], variação 1a 9m–25a 6m), foram recrutados; 168 medidas foram registradas. Os pacientes deambularam com uma média de (DP 5a 4m) e perderam a capacidade deambulatória com 8a 8m (DP 2a 1m). As avaliações de GMFCS e FMS‐5, FMS‐50, FMS‐500 se correlacionara mcom a idade (correlações de r =0, 555, –0, 617, –0, 639, –0, 662 respectivamen, p <0, 01 para todos), mas atingiram platô após a idade de 12 anos. O escore médio da EFAT foi 37, 46 (DP 7, 88) e houve aumento com a idade (correlação de Spearman r =0, 585, p <0, 01). A escala mostrou três estágios de progressão da doença. Interpretação: Neste estudo piloto, mostramos dados funcionais longitudinais sobre a deambulação e AVDs em ataxia telangiectasia, e criamos uma estrutura para uma escala fncional. Esta escala funcional se assemelhou com o curso da doença, porém maiores estudos para validação são necessaries.